A discourse-theoretic approach to story recall in aging and mild cognitive impairment. Issue 5 (3rd September 2021) - Taler, Vanessa; Davidson, Patrick S.R.; Sheppard, Christine; Gardiner, Jessie
ABSTRACT: Recall of story materials is a primary way to assess episodic memory. However, the standard scoring method may not be maximally sensitive to cognitive decline. We developed a set of 24 stories, and younger and older adults heard these stories and recalled them immediately and after a delay (Study 1). Twelve of these stories were then selected, and older adults and people with MCI completed immediate and delayed recall of these stories (Study 2). Responses were classified as veridical, gist, or distorted, and were scored by number of units and number of propositions recalled. Younger adults had higher veridical recall than older adults, and proposition-based scoring revealed higher gist recall in older than younger adults. Gist and distortion recall increased over time in older adults, but decreased in MCI. Using proposition-based scoring and distinguishing between veridical and gist responses may discriminate better between healthy older adults and people with MCI.